A perspective on Minsky moments: The core of the financial instability hypothesis in light of the subprime crisis - Alessandro Vercelli (Levy Economics Institute of Bard College, 2009)
This paper aims to help bridge the gap between theory and fact regarding the so-called 'Minsky moments' by revisiting the 'financial instability hypothesis' (FIH). We limit the analysis to the core of FIH-that is, to its strictly financial part. Our contribution builds on a reexamination of Minsky's contributions in light of the subprime financial crisis. We start from a constructive criticism of the well-known Minskyan taxonomy o f financial units (hedge, speculative, and Ponzi) and suggest a different approach that allows a continuous measure of the unit's financial conditions. We use this alternative approach to account for the cyclical fluctuations of financial conditions that endogenously generate instability and fragility. We may thus suggest a precise definition of the 'Minsky moment' as the starting point of a Minskyan process-the phase of a financial cycle when many financial units suffer from both liquidity and solvency problems. Although the outlined approach is very simple and has to be further developed in many directions, we may draw from it a few policy insights on ways of stabilizing the financial cycle.
Keywords: B50; E32; E44; G28; 330; financial instability; financial fragility; financial fluctuations; subprime crisis; Minsky moments; Minsky meltdown; speculative units; hedge units; Ponzi units; Finanzmarktkrise; Theorie